A Comparative Analyses for NRZ and RZ to the Best Performance in Optisystem Program to Cary Data Over Fiber Optics - Hasan, Hasan J. Hasan (The Journal of Multidisciplinary Research, 2023)
Data transmission has become an important issue in today’s telecommunications world. In order to get the best results in sending and receiving data via optical cable, there are various ways to improve the performance of such systems. In this paper, the simulation program (optsystem)was used to design a communication system for data transmission over a fiber optic to compare the performances of the Return to the Zero (RZ) as well as Non Return to the Zero (NRZ) for different distances. The data was sent over distances ranging from 5 km to 50 km, with an increase of 5 km for each measurement. And recording the values of both Q. factor and (BER), as well as recording eye diagram figures for each case in order to compare to get the best performance for each distance used.